Recent Studies on the Asymptotic Convergence of the Spatial Discretization for Two-Dimensional Discrete Ordinates Solutions - L. B. Barichello, C.B. Picoloto; Azmy, Y.Y. (Journal of Computational and Theoretical Transport, 2016)
n/a
n/a